Excision technique in constrained formulations of Einstein equations: collapse scenario. (March 2015) - Cordero-Carrión, I; Vasset, N; Novak, J; Jaramillo, J L
Abstract: We present a new excision technique used in constrained formulations of Einstein equations to deal with black hole in numerical simulations. We show the applicability of this scheme in several scenarios. In particular, we present the dynamical evolution of the collapse of a neutron star to a black hole, using the CoCoNuT code and this excision technique.